Proposta de plano de controle para redes ópticas de transporte utilizando LSPs hierárquicos - Bueloni, Luiz Guilherme Bergamaschi (2014)
The evolution of telecommunication networks has enabled the creation of new classes of services which keep increasing the demand to core network technologies. The requirements are more dynamism and ability to supply resources for transporting information based on demands, a feature known as BoD (Bandwidth on Demand). At the network core, Optical Transport Networks (OTN) presents advances to meet those requirements, and has been established as default network transport technology. Integrating capacities of switching and multiplexing at both optical and electrical domains, the concept of an OTNSwitch equipment emerges as a promissing solution to the core networks. However, even when the Transport Plane offers such capabilities, the existence of a Control Plane is necessary to operate equipment and to perform configuration of paths in the network. In this work we propose extentions for a GMPLS (Generalized Multiprotocol Label Switching) based Control Plane, enabling communication and compatibily with an theorical OTNSwitch equipment. We also discuss allocation of resources on demand using the concept of hierarchical LSPs.